Rotte commerciali e consumo di derrate alimentari a Taranto: le anfore e la funzione ricettiva del porto dal periodo arcaico a quello romano (VII secolo a.C. – VII secolo d.C.) - Disantarosa, Giacomo (Rei Cretariae Romanae Fautorum Acta, 2023)
By compiling the evidence for amphorae from both urban excavation contexts and underwater sites it possible to establish some details of the economic history of Taranto (Italy) over about 14 centuries, from the Archaic period to Late Antiquity, and to draw some general conclusions about the market in imported foodstuffs and the activities connected with their warehousing in the port. In some cases stratigraphic excavations have made it possible to determine some of the ways in which amphorae were given a new function once they had been emptied of their primary contents. For the most part they were reused as building materials and in burials. In the earliest phases Greek-oriental amphorae and those made in the city states of Magna Graecia were imported and circulated. After the Roman conquest of Tarentum they were supplanted by “Italic” products which were traded by preference along routes which connected the port of Taranto with the Tyrrhenian and Adriatic coasts, although Sicily was not excluded. In the Early Empire, new markets were opened up which were consolidated and reinforced in Late Antiquity, when routes and productive systems were linked to the north African territories and to the Aegean and Eastern Mediterranean.